Distribution and molecular investigation of highly thermophilic bacteria associated with cool soil environments. (1st April 2004) - Rahman, T.J.; Marchant, R.; Banat, I.M.
Abstract : In this study, both molecular and culture-based methods were used to characterize thermophilic bacteria associated with the subsurface soil environment in Northern Ireland. A total of 53 thermophilic, aerobic, sporulating and non-sporulating bacteria were isolated from subsurface soil samples obtained from two sites. They were screened by amplified ribosomal DNA restriction analysis prior to 16 S rRNA gene sequencing. The majority of the sequences were associated with Geobacillus thermoleovorans (50%) and Geobacillus caldoxylosilyticus (34.6%). Isolates F10, F20 and Tf exhibited only 93% similarity with Geobacillus toebii strain F70. Hence they may represent a new species of the genus Geobacillus .